2010
DOI: 10.1021/ic902445c
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Dynamics in Tb3+-Doped CaWO4 and CaMoO4 Crystals

Abstract: Single crystals of CaWO(4) and CaMoO(4) doped with Tb(3+) have been grown by the flux growth method. Their luminescence properties have been investigated in the 10-600 K temperature range under different experimental conditions. In spite of very similar spectra at low temperature upon excitation at 365 nm, the crystals show a very different behavior as the temperature is raised or the excitation wavelength is changed. These differences have been accounted for on the basis of models that take into consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(83 citation statements)
references
References 32 publications
4
76
0
1
Order By: Relevance
“…The observed signals are ascribed to Bi 3+ (6s 2 )?M n+ (d 0 ) MMCT (M n+ = Nb 5+ and Mo 6+ , respectively). Similar attributions of low-lying excitation signals to Bi-MMCT have been made in previous reports for the vanadates LnVO 4 :Bi 3+ (Ln = Y, Gd, La): [16][17][18][19] and the niobates LnNbO 4 :Bi 3+ (Ln = Y, Gd, La) [20][21][22].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The observed signals are ascribed to Bi 3+ (6s 2 )?M n+ (d 0 ) MMCT (M n+ = Nb 5+ and Mo 6+ , respectively). Similar attributions of low-lying excitation signals to Bi-MMCT have been made in previous reports for the vanadates LnVO 4 :Bi 3+ (Ln = Y, Gd, La): [16][17][18][19] and the niobates LnNbO 4 :Bi 3+ (Ln = Y, Gd, La) [20][21][22].…”
Section: Resultssupporting
confidence: 87%
“…It is ascribed to Bi 3+ (6s 2 )?Ti 4+ (d 0 ) MMCT. In the case of CaNb 2 O 6 :Bi 3+ and CaMoO 4 :Bi 3+ , the HFE is not observed (it is expected at about 36 000 cm À1 in the former [9] and 34 000 cm À1 in the latter [17]). The observed signals are ascribed to Bi 3+ (6s 2 )?M n+ (d 0 ) MMCT (M n+ = Nb 5+ and Mo 6+ , respectively).…”
Section: Resultsmentioning
confidence: 91%
“…Such small E could be involved only in process between very closely lying levels. Cavalli et al [33] observed similar thermal behaviour of Tb 3+ 5 D 3 luminescence decay in CaWO 4 below 100 K and indicated that the variation of decay time can have origin in thermal population of the Stark components in the 5 D 3 multiplet. In [23] the measured energies of 5 D 3 manifold in YAG were: 26 157.5 cm −1 and 26 156.1 cm −1 giving very small energy gap.…”
Section: Temperature Dependencementioning
confidence: 76%
“…This is in line with observations for other Tb 3 þ tungstates as f.i. CaWO 4 :Tb [20]. In undoped KYW only ligand-to-metal charge transfer absorption within the tungstate units is observed.…”
Section: Optical Propertiesmentioning
confidence: 94%